Thermal investigation of high-power GaAs-based laser diodes. (June 2017) - Liu, Jichuan; Wang, Cuiluan; Liu, Suping; Ma, Xiaoyu
Abstract: The thermal characteristics of high-power AlGaAs/GaAs laser diodes (LDs) at high current (2–10 A) are studied with electrical transient method. The temperature rise increases linearly with the current. The thermal resistance of chip is the largest proportion of total thermal resistance. By increasing the width of the chip from 500 to 800 μ m, the temperature rise and thermal resistance decrease by 8.5% and 8.8%, respectively.